2020
DOI: 10.3390/microorganisms8081141
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Changes Due to Grape Seed Extract Diet Improved Intestinal Homeostasis and Decreased Fatness in Parental Broiler Hens

Abstract: In poultry, the selection of broilers for growth performance has induced a deterioration in the health of the parental hens associated with poor reproductive efficiency. To improve these parameters, we administered to laying parental broiler hens a regular diet supplemented or not (Control) with a moderate (1%) or a high level (2%) of grape seed extract (GSE). The 1% GSE diet was administered from a young age (from 4 to 40 weeks of age) and the high level of 2% GSE was administered only during a 2-week period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
(102 reference statements)
1
7
0
Order By: Relevance
“…Additionally, Viveros et al (2011) noted that broiler chicks fed the diet supplemented with grape seed extract increased ileal Lactobacillus abundance of broiler chicks. Grandhaye et al (2020) found an increase in the relative abundance of Bifidobacteriaceae, Lactobacilliaceae , and Lachnospiraceae in the intestine of layers caused by supplementing grape seed extract to the diet. Therefore, herbal extract blend used in this study had a regulatory effect on the cecal microbiota of broiler chicks.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, Viveros et al (2011) noted that broiler chicks fed the diet supplemented with grape seed extract increased ileal Lactobacillus abundance of broiler chicks. Grandhaye et al (2020) found an increase in the relative abundance of Bifidobacteriaceae, Lactobacilliaceae , and Lachnospiraceae in the intestine of layers caused by supplementing grape seed extract to the diet. Therefore, herbal extract blend used in this study had a regulatory effect on the cecal microbiota of broiler chicks.…”
Section: Discussionmentioning
confidence: 94%
“…Grape seed is a by-product in the juice and wine industry. Dietary supplementation of grape seed extract has been reported to regulate the composition of intestinal microbiota ( Qamar et al, 2020 ), regulate the antioxidant status of the body ( Qamar et al, 2020 ), improve immune response ( Farahat et al, 2017 ), enhance production performance ( Grandhaye et al, 2020 ), and increase nutrient digestibility ( Brenes et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, polyphenols are poorly absorbed in the small intestine and therefore represent substrates available to the lower tract of the intestine 23 , 67 . Specific phenolic monomers resulting from tannins fermentation by the gut microbiota were thus found in excreta of broiler chickens 23 and in the blood of broiler hens 63 receiving grape extracts. Similarly, the administration of a blend of AA with GSE was recently found to affect the piglet gut microbiota metabolism 28 .…”
Section: Discussionmentioning
confidence: 97%
“…Functional AA and polyphenols share similar benefits on the gut health, resulting in possible additive effects when used in combination. For instance, GSE and Thr can both contribute to the mucus defense of the birds 63 .…”
Section: Discussionmentioning
confidence: 99%
“…OPC from Rhodiola rosea can reduce the releases of pro-inflammatory cytokines, lipids and antioxidant capacity to against the atherosclerosis in rats ( Zhou et al, 2018 ). Supplementation with OPC can improve the production performance and the egg quality of layer chickens by promoting the immune responses of the intestinal mucosa (Barbe et al, 2020b; Grandhaye et al, 2020 ). Furthermore, OPC-derived from GSE has been shown to prevent disequilibrium of bone metabolism in OVX animals by improving the bone healing for maintaining bone health ( Tenkumo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%